IMPLEMENTASI KURIKULUM 2013 PADA ANAK TUNAGRAHITA DI SLB AC - SUSANTI, LINDA (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Curriculum 2013 was the developing of the previous curriculum however it was emphasized to the enhancement and balance between soft skill and hard skill involving the aspects of attitude competence, skill, and knowledge. The implementation of curriculum 2013 was applied to not only regular or general school but special school as well. The purpose of this research was to describe the implementation of curriculum 2013, the teachers’ role, and the problem faced in implementing curriculum 2013 to mentally retardation children in SLB AC Dharma Wanita Sidoarjo. The research result could be concluded that 1) the implementation of curriculum 2013 to mentally retardation children in SLB AC Dharma Wanita Sidoarjo could not be stated perfect yet and there was still several concepts of the previous curriculum used. In the academic year 2015-2016, not all classes applied this curriculum 2013 as the principle of learning curriculum however only several classes had implemented it i.e. class 1 and class 4 SDLB, 2) the teacher’s role in indicating that teachers in learning program had already made a set of learning such as annual program, semester program, effective week details, syllabus, and learning plan (RPP). In addition, the teacher who had role as the educator also guided the students in learning which applied curriculum 2013 identical with the scientific approach, the teacher strived to apply this scientific approach to mentally retardation children although in the application it did not run maximally yet because of the limitedness of mentally retardation children, 3) the problem faced such as less complete teacher and student books available, less complete education media and lack of teacher’s understanding about arranging the learning set based on curriculum 2013.   Keywords: Implementation, curriculum 2013